A comparison of molecular markers and morphology for Neidium taxa (Bacillariophyta) from eastern North America. Issue 3 (2nd May 2017) - Lefebvre, Keely E.; Hamilton, Paul B.; Pick, Frances R.
Abstract : Historically, a morphological species concept has applied shape subjectively in the delimitation of diatom species. This has led to confusion between taxa within the benthic diatom genus Neidium . Samples from Ontario, Quebec, Nova Scotia, Newfoundland (Canada) and New York (USA) were examined for Neidium taxa under LM and SEM. Fourier shape analysis showed that shape as a taxonomic character was not able to discern all species. Isolated individuals from the samples were amplified and sequenced for three chloroplast molecular markers ( rbcL, psbC, and psbA ) and one nuclear ribosomal molecular marker (18S). Phylogenetic reconstructions were completed with the concatenated chloroplast and 18S dataset using Maximum Likelihood and Bayesian analyses. The concatenated chloroplast dataset exhibited a species‐level resolution phylogeny of Neidium taxa. The 18S dataset had a lower level of sequence divergence and was unable to differentiate between Neidium taxa. We present emended species descriptions and sequence data for four previously described species: Neidium sacoense, N. longiceps, N. fossum, and N. affine . We describe three novel species ( Neidium lowei, N. promontorium, and N. potapovae ) and identify two forms with unique molecular signatures. The distinguishing features of N. lowei are its size, valve shape, and longitudinal canal structure. Distinguishing features of N. promontorium are its valve shape, longitudinal canal and apex formation, and surface depression along the axial area. Neidium potapovae is distinguished by its size, formation of valve and apices and single longitudinal canal. This paper demonstrates how future phylogenetic treatments using single cell multigene sequencing can help resolve taxonomic confusion within diatoms.